Makna Qarar dalam Al-Qur - Laraswati, Laraswati (Syams, 2023)
In the Qur'an there are many words that have various meanings, one of which is synonymouswith a place of residence, namely qarār which can be used for a solid place, an eternal placeand the worst place. When they are in different sentences, they have different meanings. Thisis influenced by the context that surrounds it. This uniqueness motivates the author toresearch and try to analyze the meaning of qarār contained in several related verses. Based onthe background, the formulation of the problem in this study is: How does qarār in theQur'an use Muhammad Syahrur's semantic analysis? The purpose of this study was todetermine the meaning of qarār in the Qur'an from Muhammad Syahrur's semanticapproach. This research is qualitative or library research. By using descriptive-analysis/thematic methods, and using Muhammad Syahrur's semantic approach with twosteps of use, namely paradigmatic syntagmatic analysis. The results of the findings of theword qarār which means the origin of the place of residence or determination. Basedon Muhammad Syahrur's semantic analysis at the paradigmatic level compared tothe word Maskan the meaning of Qarār is a fixed place that does not move around,then at the syntagmatic level analysis it is associated with the words Makiin, ardho,Dar, Bi'sa, ma'iin, and lahaamin meaning Qarār is a solid place, namely thewomb, a place for human beings to live, namely the earth, an eternal place, namelythe hereafter, a bad place, namely hell, a high place, namely Damascus, BaitulMaqdis, Palestine, and has no foothold, then with diachronic synchronic analysis itcan be It is known that in the pre-Qur'anic period the meaning of Qarār was themost comfortable seat like sitting on a camel, during the Qur'anic period it was aplace to live, in the post-Qur'anic period or today it is a place that Allah has createdto live in it and not will move around again if it enters that place. So the word qarārwill always be connected with the vocabulary that surrounds the verse through theparadigmatic and syntagmatic relations. So that the word qarār can be understoodproperly and correctly by the reader.